Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper assesses the evolution of Eastern Caribbean Currency Union (ECCU) real exchange rates over time, and examines whether the region has lost competitiveness. The main finding is that there is little evidence of overvaluation of the Eastern Caribbean (EC) dollar. The relationship summarized above permits the calculation of equilibrium current account balances or norms. The financing of ECCU current account imbalances appears stable. This paper also provides evidence on the distinctive impact that tourism plays in the determination of the real exchange rate in tourism-driven economies.